Strengthening the influenza vaccine virus selection and development process: Report of the 3rd WHO Informal Consultation for Improving Influenza Vaccine Virus Selection held at WHO headquarters, Geneva, Switzerland, 1–3 April 2014. Issue 36 (26th August 2015) - Ampofo, William K.; Azziz-Baumgartner, Eduardo; Bashir, Uzma; Cox, Nancy J.; Fasce, Rodrigo; Giovanni, Maria; Grohmann, Gary; Huang, Sue; Katz, Jackie; Mironenko, Alla; Mokhtari-Azad, Talat; Sasono, Pretty Multihartina; et al.
Abstract: Despite long-recognized challenges and constraints associated with their updating and manufacture, influenza vaccines remain at the heart of public health preparedness and response efforts against both seasonal and potentially pandemic influenza viruses. Globally coordinated virological and epidemiological surveillance is the foundation of the influenza vaccine virus selection and development process. Although national influenza surveillance and reporting capabilities are being strengthened and expanded, sustaining and building upon recent gains has become a major challenge. Strengthening the vaccine virus selection process additionally requires the continuation of initiatives to improve the timeliness and representativeness of influenza viruses shared by countries for detailed analysis by the WHO Global Influenza Surveillance and Response System (GISRS). Efforts are also continuing at the national, regional, and global levels to better understand the dynamics of influenza transmission in both temperate and tropical regions. Improved understanding of the degree of influenza seasonality in tropical countries of the world should allow for the strengthening of national vaccination policies and use of the most appropriate available vaccines. There remain a number of limitations and difficulties associated with the use of HAI assays for the antigenic characterization and selection of influenza vaccine viruses by WHOCCs. Current approaches to improving the situation include the more-optimal use of HAI and other assays; improved understanding of the data produced by neutralization assays; and increased standardization of serological testing methods. A number of new technologies and associated tools have the potential to revolutionize influenza surveillance and response activities. These include the increasingly routine use of whole genome next-generation sequencing and other high-throughput approaches. Such approaches could not only become key elements in outbreak investigations but could drive a new surveillance paradigm. However, despite the advances made, significant challenges will need to be addressed before next-generation technologies become routine, particularly in low-resource settings. Emerging approaches and techniques such as synthetic genomics, systems genetics, systems biology and mathematical modelling are capable of generating potentially huge volumes of highly complex and diverse datasets. Harnessing the currently theoretical benefits of such bioinformatics ("big data") concepts for the influenza vaccine virus selection and development process will depend upon further advances in data generation, integration, analysis and dissemination. Over the last decade, growing awareness of influenza as an important global public health issue has been coupled to ever-increasing demands from the global community for more-equitable access to effective and affordable influenza vaccines. The current influenza vaccine landscape continues to be dominated by egg-based inactivated and live attenuated vaccines, with a small number of cell-based and recombinant vaccines. Successfully completing each step in the annual influenza vaccine manufacturing cycle will continue to rely upon timely and regular communication between the WHO GISRS, manufacturers and regulatory authorities. While the pipeline of influenza vaccines appears to be moving towards a variety of niche products in the near term, it is apparent that the ultimate aim remains the development of effective "universal" influenza vaccines that offer longer-lasting immunity against a broad range of influenza A subtypes.